THE IMPACT OF TERRORISM AS A SOCIAL PHENOMENON ON THE POLITICAL AND RELIGIOUS SPHERES OF THE SOCIETY - Bogmatsera, Eduard; Savtsova, Natalya; Kurbanov, Aiden (Revista Inclusiones, 2019)
The article looks at the origins of terrorism as a social phenomenon, as well as the historical development of its impact on the political and religious spheres of the society. Additionally, the authors analyze some specific features of how terrorism emerged and developed as a social and political phenomenon over the history of different countries. The article demonstrates an approach, according to which the phenomenon of terrorism, as the majority of social phenomena, has naturally gone through a few stages of evolution, starting from its inception in the ancient era to the modern stage of development of the world civilization. At each stage of its evolution, terrorism as a sociopolitical phenomenon is determined by factors and conditions that emerge and take shape in the course of development of human civilization in the context of specific historical and territorial development of individual states. In the first place, modern terrorism is conditioned by the development of globalization processes.